The Use of Reading Aloud Technique to Improve Students’ Speaking Skill: Study at 7th Grade of SMP N 37 Semarang in Academic Year 2021/2022 (Undergraduate Conference on Applied Linguistics, Linguistics, and Literature, 2022)
This research focuses on improving students’ speaking skill by using Reading Aloud Technique to see how far the improvement of students speaking skill for 7th grade students of SMP N 37 Semarang in academic year 2021/2022. In this case, the researchers adopted Quantitative Research. The researchers ran the research by forming two groups consisting of experimental and control group. the researchers took 7G as Experimental Group and 7H as a Control Group. The control group was treated without using Reading Aloud Technique, and the other group, which is the experimental group was treated by using Reading Aloud Technique. In this research, the researchers used speaking test and writing test in order to get the data. The speaking skill of the 7th grade students of SMP N 37 Semarang in the academic year 2021/2022 who are taught by using reading aloud technique increased. While, the students who was taught without using reading aloud technique increased but was not significant. It can be concluded that there were significant differences in their speaking skill between the students who was taught using reading aloud technique and there who was taught without using reading aloud technique. It was proven by the t-test score that was higher than t-table score which was 3.28 2.029. So, the positive hypothesis (Ha) is accepted.
Keywords: improve, speaking skill, reading aloud